FRI0290 Pro-inflammatory cytokines promote global and gene-specific changes in dna methylation in salivary glands from sjÖgren's syndrome patients. (12th June 2018) - Lagos, C.; Aguilera, S.; Carvajal, P.; Jara, D.; Castro, I.; González, S.; Urzua, U.; Barrera, M.J.; Molina, C.; Leyton, C.; González, M.-J.
Abstract : Background: Salivary glands (SG) from Sjögren's syndrome (SS)-patients show chronic inflammation and altered unfolded protein response (UPR). Pro-inflammatory cytokines induce epigenetic changes including DNA methylation, a dynamic and complex process where cytosines of CpG sites are methylated (5mC) by DNA methyltransferases (DNMT), and then hydroxymethylated (5hmC) by TET enzymes. Objectives: To determine DNA methylation in promoters of specific UPR genes and levels of 5mC, 5hmC, DNMT and TET enzymes in labial-SG from SS-patients and cytokine effects on global DNA methylation and DNA methylation of specific gene promoters in human SG cells Methods: SG biopsies from 23 SS-patients and 15 controls were analysed. 5mC and 5hmC levels were assessed by immunofluorescence (IF), quantified independently in epithelial and inflammatory cells and correlated with focus score. mRNA levels of DNA methyltransferases (DNMT1, DNMT3a, and DNMT3b), and dioxygenases TET1, TET2 and TET3 were determined by RT-qPCR. The in situ protein levels of these enzymes were evaluated by IF. Specific DNA methylation of IRE1α, XBP-1, GRP78, ATF4 and ATF6α gene promoters was evaluated by MS-HRM. Human SG cells (HSG) and 3D-acini were incubated with 1 or 10 ng/mL TNF-α and IFN-γ for 24 hour. Levels of 5mC, 5hmC, methylation of specific gene promoters and transcript levels of UPR molecules, DNMTs and TETs were determined. Results: LSG epithelial cells from SS-patients showed significant increase of DNA hydroxymethylation and decrease of DNA methylation. Their 5hmC levels were positively and 5mC levels inversely correlated with focus score. Inflammatory cells showed high levels of 5mC and DNMTs and low levels of 5hmC. Increased mRNA levels of DNMT1, DNMT3a, and TET2 and a significant decrease of TET1 and TET3 were observed. Protein levels of TET2 were significantly higher in LSG epithelial cells from SS-patients. The above results were reproduced in HSG cells where cytokine stimulation increased TET2 and 5hmC and decreased 5mC levels. SS-patients SG and 3D-acini stimulated with cytokines, revealed an inverse correlation between gene promoter DNA methylation and transcript levels of IRE1α, XBP-1, GRP78, ATF4 and ATF6α. Conclusions: Pro-inflammatory cytokines promoted increase of 5hmC and decrease of 5mC in SG epithelial cells likely by inducing TET2 expression. Global DNA hypomethylation have also been observed in other autoimmune diseases, where some specific genes appear to be hypermethylated. Our results showed a concordance between the methylation of UPR gene promoters and its transcriptional regulation, which was modulated by cytokines. High DNMTs protein levels observed in inflammatory cells are consistent with high levels of 5mC suggesting that increased DNMTs transcript levels in LSG from SS-patients come from inflammatory cells. 5mC has been associated with transcriptional repression, while 5hmC with transcriptional activation, therefore, we postulate that changes of DNA hydroxymethylation resulting from altered levels of TET2 could have an etiopathogenic role in Sjögren's syndrome. Acknowledgements: Fondecyt-1160015, Fondecyt-Iniciación-11170049, IC, Fondecyt-Postdoctorado-3170023, MJB. Disclosure of Interest: None declared